PENGARUH BIAYA PRODUKSI TERHADAP PENJUALAN PADA CAFÉ SANTOSA DFS DEPARTEMEN SANTOSA HOSPITAL BANDUNG CENTRAL - Euis Hernawati; Febryana Suryana (JEBS (Journal of Economic and Business Student), 2022)
ABSTRACT                This research  aims to determine the level of  influence of production costs towards sales at Cafe Santosa DFS Department Santosa Hospital Bandung Central.The method used in this study is a quantitative analysis, which is a method that seeks to provide an overview of systematic, factual and accurate, with taking a sample for period 2015 at Cafe Santosa DFS Department Santosa Hospital Bandung Central.            From this research formed the estimated regression models  Y = 915709,575 + 2,756X which any increase in production cost Rp 1 million, then the sales funds will raise funds amounting Rp 3.671.709,575 and when the production cost is equal to zero, then the sales funds Rp 915.709,575. And the coefficient of determination obtained 97,90% which means that 97,90%  of  sales be affected by the production cost, while the remaining 2,10% sales can be affected by other variabels.